Efficacy and safety of treatment of chronic hepatitis C with sofosbuvir and ribavirin with or without peginterferon: a French prospective real-life cohort study of unselected 211 patients. Issue 10 (October 2019) - Garioud, Armand; Heng, Ratmony; Amiot, Xavier; Rémy, André-Jean; Ollivier-Hourmand, Isabelle; Mokhtari, Camelia; Medmoun, Mourad; Renou, Christophe; Zougmoré, Honoré; Pulwermacher, Philippe; Lucidarme, Damien; Rosa-Hézode, Isabelle; et al.
Abstract : Introduction: Sofosbuvir is the first directly-acting antiviral for the treatment of hepatitis C virus. First, the regimens were combinations with sofosbuvir+ribavirin (SR) or with sofosbuvir+ribavirin and pegylated-interferon α-2a (SPR) with cure rates around 90%. The aim of this study was to report the results of these combinations in 'real-life' in France. Materials and methods: Main features of patients treated with SR or SPR in 24 hospitals were collected. Undetectable hepatitis C virus week 12 viral load after treatment defined sustained virological response (SVR12). Statistics were performed using StatView software for descriptive analysis and χ 2 for the sub-groups comparisons. Results: Two hundred and eleven patients were analyzed. The average age was 56.1. One hundred and seventy-one (89%) patients had a fibrosis score of at least 3. Seventy-nine patients were infected by a genotype 1 (G1). One hundred and thirteen patients were treated with SR and 95 with SPR. In naive patients: with SPR for 12 weeks, SVR12 was 93% in G1, 100% in G3 and 83% in G4. With SR for 12 weeks, SVR12 was 100% in G2 patients (6/6). The safety of these regimens was satisfactory with only two patients who had to stop P due to severe side effects. Multivariate analysis shows a higher SVR in SPR versus SR (odds ratio = 1.28; P = 0.05) and in G2 or G3 versus others (odds ratio = 1.56; P = 0.04). Moreover, Child–Pugh score B or C ( P = 0.02), platelets count under 100G/l ( P = 0.05) or a past event of ascites ( P = 0.04) was independently associated with less SVR. Conclusion: This multicenter large study confirms the good results of SR for 12 weeks in G2 naive patients. Finally, a decompensated cirrhosis, a past event of ascites and a baseline low platelet count were strongly associated with poor response.